2011
DOI: 10.1111/j.1600-051x.2011.01779.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple applications of flurbiprofen and chlorhexidine chips in patients with chronic periodontitis: a randomized, double blind, parallel, 2‐arms clinical trial

Abstract: AimThe aim of the present randomized, double blind, parallel, 2-arm clinical study was to examine the safety and efficacy of frequent applications of chlorhexidine chip (CHX) and flurbiprofen chip (FBP) in patients with chronic periodontitis.MethodsSixty patients were randomized into CHX and FBP groups. Following OHI and scaling and root planing (SRP), baseline pocket depth (PD) measurements, gingival recession and bleeding on probing (BOP) were performed and repeated at week 4 and 8. The assigned chip was pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
1
13
1
1
Order By: Relevance
“…Mean PPD reduction from baseline to week 11 visit for the SRP plus CHX group was 1.9 ± 0.32 mm similar to the results obtained by Kondreddy K et al, [30] where he noted a mean reduction in probing pocket depth between 0 and 90 th day of 1.6±0.5 mm and 1.26+1.19 mm as seen by Grover V et al, [17]. Mean PPD reduction of 2.08 mm was noted in a similar study after 8 weeks and could be attributed to the repeated placement of CHX chips as opposed to the single time placement in the present study [31]. An additional PPD reduction of 0.8 mm was obtained in the SRP plus CHX group as compared to the SRP group at 11 weeks.…”
Section: Discussionsupporting
confidence: 75%
“…Mean PPD reduction from baseline to week 11 visit for the SRP plus CHX group was 1.9 ± 0.32 mm similar to the results obtained by Kondreddy K et al, [30] where he noted a mean reduction in probing pocket depth between 0 and 90 th day of 1.6±0.5 mm and 1.26+1.19 mm as seen by Grover V et al, [17]. Mean PPD reduction of 2.08 mm was noted in a similar study after 8 weeks and could be attributed to the repeated placement of CHX chips as opposed to the single time placement in the present study [31]. An additional PPD reduction of 0.8 mm was obtained in the SRP plus CHX group as compared to the SRP group at 11 weeks.…”
Section: Discussionsupporting
confidence: 75%
“…More recently, we have reported (Machtei et al. ) on the clinical response to a similar intensive protocol of chlorhexidine chips placement around teeth: Mean PD reduction was incredibly similar (2.09 mm) compared with that around implants in this study (2.13 mm); In contrary, CAL gain in this study (2.18 mm) was much greater than what we have achieved around teeth (1.66 mm). This phenomenon would require further research as it may lend some clues to the less favourable response to therapy often reported with dental implants (Lang & Berglundh ).…”
Section: Discussioncontrasting
confidence: 57%
“…Recently (Machtei et al 2011), we have been able to demonstrate that frequent application of biodegradable matrix containing chlorhexidine (PerioChip ® ; Dexcel Pharma, Or-Akiva, Israel) in patients with chronic periodontitis with PD ! 5 mm resulted in a sizeable improvement in mean PD (2.1 mm) and gain in CAL (1.7 mm).…”
mentioning
confidence: 99%
“…Attempts to address this issue have included repeated administration of the antimicrobial (Machtei et al. ). In this trial, however, repeated USI was performed at sites with PPD ≥4 mm at the 3‐, 6‐ and 9‐month follow‐up for both the test and control groups; the short duration of the additive benefit of SRD needs to be interpreted in this context.…”
Section: Discussionmentioning
confidence: 99%